Giant epidermal cyst of the arm: a rare presentation - Patel, Shaan (BMJ Case Rep, 2018)
A giant epidermal cyst is a benign soft tissue mass commonly involving the trunk, hand and face. The authors report a rare presentation of a 69-year-old man who presented with a painful, slow-growing left arm mass for 30 years duration. Examination revealed a large, mobile, soft tissue mass of the lateral aspect of the left arm. MRI showed a large, cystic left arm soft tissue mass. The mass was excised and the diagnosis of a giant epidermal cyst was made based on imaging and histopathology after surgical resection. The mass measured 9.5 cm x 8 cm x 4 cm, which is the largest reported giant epidermal cyst of the upper extremity.